Eksplorasi Wisata Budaya Berbasis Kearifan Lokal di Desa Wisata Wates Jaya, Kabupaten Bogor, Jawa Barat - Inti Krisnawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Wates Jaya Tourism Village is one of the tourism villages in Bogor Regency. This village is located in the southernmost tip of Bogor Regency, directly adjacent to Sukabumi Regency and located at the foot of Mount Gede Pangrango and Mount Salak. This village has beautiful nature, cool fresh air, enchanting scenery, and also clear water. In this village, lies the spring from which the flow the Cisadane river begins. The Cisadane River is one of the major rivers in Tatar Pasundan, which flows through Bogor Regency to Tangerang and empties into the Sea Java. This research was conducted with the purpose of exploring local wisdom in Wates Jaya Tourism Village, to be developed as a cultural tourism attraction. This research is descriptive qualitative, and was carried out using the method survey, FGD, interview, observation and literature study. Based on research, Tourism VillageWates Jaya turns out to have a unique culture that can be developed as a tourist attraction. Residents in this village, the community is still dominant in speaking with Sundanese compared to Bahasa Indonesia. They still believe in myths that are magical. Some of the residents' livelihoods are farming and gardening, houses can still be found in woven bamboo walls with traditional kitchen and utensils, traces of various traditional games, traditional snacks, and the martial arts known as Kelid.